Boarding School Entrepreneurship Curriculum - Ade Hasim; Ulil Amri Syafri (Intiqad: Jurnal Agama dan Pendidikan Islam, 2023)
The purpose of writing this article is to find out the entrepreneurial curriculum and learning process both in Al-Kasyaf Bandung Boarding School and YBM PLN Thursina Bogor Entrepreneur Boarding School in building the character of entrepreneurial independence of students which includes curriculum, learning activities and student activities. The research used was field research using descriptive qualitative research methods. Data was obtained through the process of observation, direct interviews and documentation. From the research conducted, the first result is that in the application of different entrepreneurship curricula, Al-Kasyaf Bandung Islamic Boarding School and YBM PLN Thursina Bogor Entrepreneurial Boarding School have the same goal, which is to form students' attitude of independence and responsibility in entrepreneurship, which includes having mental courage in entrepreneurship, being able to manage time between running business activities and learning activities, and being able to manage finances without depending on others. Second, the learning activities of students in religion-related subjects are almost the same as those in ordinary boarding school, which use memorisation, sorogan and bandongan methods. In entrepreneurial learning, in addition to direct coaching and training, students also receive motivation from guardians both directly (through meetings) and indirectly (through Whastapp social media). Thirdly, student activities in the boarding school environment, apart from deepening religious knowledge by participating in book discussions, Khitobah and seven-minute lectures, and giving lectures to the community, are also filled with managing independent businesses owned by the boarding school.